THE INFLUENCE OF WORK ENVIRONMENT AND DISCIPLINE ON WORK PRODUCTIVITY IN THE IMPLEMENTATION OF THE COMPLETE SYSTEMATIC LAND REGISTRATION PROGRAM (PTSL) IN BANDARAN VILLAGE, WINONGAN DISTRICT, PASURUAN REGENCY - Yolanda, Tarisa Endah; Pudyaningsih, Agnes Ratna; Wahyuni, Hari (Yayasan Education and Social Center, 2025)
Land registration is a legal process involving the registration of ownership or rights to land at authorized government institutions, such as land offices. The Complete Systematic Land Registration Program (PTSL) is one of the government's efforts to improve the quality of land services and expedite the land registration process. The final stage of land registration is the issuance of a land certificate as proof of title. The land certificate serves as official evidence that provides legal certainty regarding the ownership or rights stated therein. This study aims to determine the influence of the work environment and discipline on work productivity in the implementation of the Complete Systematic Land Registration Program (PTSL) in Bandaran Village, Winongan District, Pasuruan Regency. The analysis used is research instrument testing, descriptive analysis, classical assumption testing and hypothesis testing. Based on the results of the study, the R Square value was obtained at 67.8%, which means that work productivity can be explained by 67.8% by the work environment and discipline. The work environment and discipline have a significant effect on work productivity simultaneously with an F count value of 33.63 and an F table value of 3.29 and a significance value of 0.000 <0.05 indicating that Ha1 is accepted. The results of the work environment hypothesis test (X1) state a significance value of 0.025 <0.05 indicating that the work environment has a significant effect on work productivity. The results of the work discipline hypothesis test (X2) state a significance value of 0.015 <0.05 indicating that discipline has a significant effect on work productivity.